Persistent Purine Metabolic Abnormality Induces the Aggravation of Visceral Inflammation and Intestinal Microbiota Dysbiosis in Magang Goose - Ma, Weiqing; Zhou, Lingjuan; Li, Yu; Xia, Daiyang; Chen, Jianying; Chen, Junpeng; Jiang, Xianzhi; Qin, Jiangfan; Zhao, Yujie; Zhang, Xiufen; Wang, Heng; Fu, Yang; et al. (Frontiers in Veterinary Science, 2021)
Gout is a disease involving abnormal purine metabolism that is widespread in mammals and birds. Goose is especially susceptible for gout in early stage. However, few study investigated ontogenetic pattern of goslings with purine metabolic abnormality. Our study was conducted to investigate whether persistent purine metabolic abnormality would lead to aggravation of visceral inflammation and intestinal microbiota dysbiosis in goose. A total of 132 one-day-old Magang geese were randomly divided into 6 replicates and fed a high-calcium and protein meal-based diet from 1 d to 28 d. The experiment lasted for 28 days. Liver and kidney damages were observed in 14 and 28-day-old Magang geese, and liver inflammation was increased with age growing. In 28-day-old Magang geese, serum CAT and liver GSH-Px activity were significantly reduced. Furthermore, jejunum intestinal barrier was impaired and the abundance of Bacteroides was significantly reduced at the genus level. Collectively, the high-calcium and high-protein (HCP) meal-based diet caused liver and kidney damage in 28-day-old Magang geese, leading to hyperuricemia and gout symptoms, and the intestinal barrier is impaired and intestinal flora disorders.